Análise comparativa de integridade de poço entre o regulamento técnico SGIP e a NORSOK STANDARD D-010 - Azevedo, Matheus Medeiros de (2016)
Well integrity refers to its ability to prevent an uncontrolled flow of fluid across the formations or between the reservoir and the surface by means of a set of techniques and equipment to establish safety barriers and It is very important for protection of human life, the environment and union assets, the contract operator and third parties involved. Around the world, there are some documents that regulate the oil industry regarding integrity well. In this paper will be highlighted the Regulamento Técnico do Sistema de Gerenciamento de Integridade de Poço (SGIP) and the guideline NORSOK D-010. Although they treat the same subject and their ultimate objective are the same, they present some different views and definitions. This paper consists in performing a comparative and comprehensiveness analysis between the SGIP and NORSOK D-010 during the life stages of a well, as well the concepts that the document deal with, thus allowing a view of how the well integrity is treated in both countries, thus allowing a broader view on the subject. The Guideline presents a prescriptive character influencing the way in which the company manages their projects, giving greater conformity between them, while the SGIP gives freedom to the company, by means of risk assessment, the way in which the contract operator establishes Its well Integrity management, demonstrating a liberal character.